2014
DOI: 10.1111/ajps.12117
|View full text |Cite
|
Sign up to set email alerts
|

Policy‐Induced Risk and Responsive Participation: The Effect of a Son's Conscription Risk on the Voting Behavior of His Parents

Abstract: When do government policies induce responsive political participation? This study tests two hypotheses in the context of military draft policies. First, policy-induced risk motivates political participation. Second, contextual-level moderators, such as local events that make risk particularly salient, may intensify the effect of risk on participation. I use the random assignment of induction priority in the Vietnam draft lotteries to measure the effect of a son's draft risk on the voter turnout of his parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…First, one body of literature is interested in political engagement and participation, including turnout, party membership, contact to politicians, political efficacy, and civic participation (for an introduction to the literature on policies and civic participation, see Campbell, ). These studies focus on how policies provide resources reducing the cost of participating in politics, specific incentives for people to participate, as well as information that makes people more likely to engage in politics (Davenport, ; MacLean, ; Mettler, ; Mettler & Welch, ; Munoz, Anduiza, & Rico, ; Shore, ).…”
Section: Outcomes and Mechanisms In Policy Feedback Studiesmentioning
confidence: 99%
“…First, one body of literature is interested in political engagement and participation, including turnout, party membership, contact to politicians, political efficacy, and civic participation (for an introduction to the literature on policies and civic participation, see Campbell, ). These studies focus on how policies provide resources reducing the cost of participating in politics, specific incentives for people to participate, as well as information that makes people more likely to engage in politics (Davenport, ; MacLean, ; Mettler, ; Mettler & Welch, ; Munoz, Anduiza, & Rico, ; Shore, ).…”
Section: Outcomes and Mechanisms In Policy Feedback Studiesmentioning
confidence: 99%
“…In some cases, we think they do. One example is Davenport (2015), who examines the effect of casualties and low draft numbers on parents' turnout during the Vietnam War. She finds that parents whose children are at high risk of being drafted (low lottery numbers) and who live in towns that have casualties, are more likely to turn out.…”
Section: Frequency and Disclosure Of Suppression Effects In Observatimentioning
confidence: 99%
“…Others have found that the effect of casualties on war support varies according to casualty trends (Gartner ), framing of the war's costs (Boettcher and Cobb ), inequalities in the composition of casualties (Kriner and Shen ), and elite cues (Berinsky ; Zaller ) ; Davenport ; Gartner and Segura ). By increasing the salience of casualties, recent information about casualties that happen close to home has a greater effect than being informed about those that are temporally and spatially distant.…”
Section: War Attitudes and Political Behaviormentioning
confidence: 99%
“…Although scholars have devoted considerable attention to war and vote choice, much less research has focused on voter participation. Some studies have examined turnout in the context of a single conflict or country (Davenport ; Karol and Miguel ; Kriner and Shen ), but to our knowledge no research has examined the effect of casualties on turnout cross‐nationally in established democracies.…”
Section: War Attitudes and Political Behaviormentioning
confidence: 99%